2013
DOI: 10.1371/journal.pone.0072210
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A1 Modulates the Expression of Vascular Endothelial Growth Factor and Promotes Hormone-Dependent Growth and Angiogenesis of Breast Cancer

Abstract: Alterations in cellular pathways related to both endocrine and vascular endothelial growth factors (VEGF) may contribute to breast cancer progression. Inhibition of the elevated levels of these pathways is associated with clinical benefits. However, molecular mechanisms by which endocrine-related pathways and VEGF signalling cooperatively promote breast cancer progression remain poorly understood. In the present study, we show that the A-type cyclin, cyclin A1, known for its important role in the initiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…During normal phase progression and at key cell-cycle transition phases, specific cyclins are activated. Aberrant activation of cyclins can lead to cancer formation [21][22][23]. In the current study, increased ratio of S phase cells and decreased ratio of G0/G1 phase cells were detected, meanwhile decreased expression of cyclin D1 and increased expression of cyclin A were observed in THP-1 cells after treated with PD.…”
Section: Discussionsupporting
confidence: 52%
“…During normal phase progression and at key cell-cycle transition phases, specific cyclins are activated. Aberrant activation of cyclins can lead to cancer formation [21][22][23]. In the current study, increased ratio of S phase cells and decreased ratio of G0/G1 phase cells were detected, meanwhile decreased expression of cyclin D1 and increased expression of cyclin A were observed in THP-1 cells after treated with PD.…”
Section: Discussionsupporting
confidence: 52%
“…In metastatic PC3 cells, cyclin A1 is functionally associated with VEGF and MMP2/MMP9 (47). Recently, we reported that cyclin A1 interacts with ERa to promote breast cancer progression in xenograft mouse models (48). Cyclin A1 function is required for hematopoietic stem and progenitor cells (HSPC) to home to their bone marrow niches (49).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced expression of cyclinA1 is also associated with aggressive, metastatic and invasive attributes of human cancer cells . c‐myb overexpression is associated with metastasis of HCC and other cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced expression of cyclinA1 is also associated with aggressive, metastatic and invasive attributes of human cancer cells. [60][61][62] c-myb overexpression is associated with metastasis of HCC and other cancers. 63,64 So, KV130/131MI may partly contribute in HCC metastasis via inducing expression of p27, cyclinA1 and c-myb (Figure 4).…”
Section: Discussionmentioning
confidence: 99%